2017
DOI: 10.1093/eurpub/ckx092
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Zika virus risk in Germany in 2016

Abstract: This study showed that fear of contracting ZIKV is not a major deterrent for travelling to high-risk areas. Pregnant women are appropriately concerned about the risk of ZIKV. Studies modelling the further spread of ZIKV need to account for these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…A May 2016 online panel survey in a German state found that two‐thirds saw their infection risk in an affected country as “quite” or “highly likely,” but of those, three‐quarters were willing to travel to the Olympics—about to occur in Brazil, then the center of Zika cases—if they won a free ticket. Pregnant women were less willing (36%) than nonpregnant women (78%) to take this trip (Obenauer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A May 2016 online panel survey in a German state found that two‐thirds saw their infection risk in an affected country as “quite” or “highly likely,” but of those, three‐quarters were willing to travel to the Olympics—about to occur in Brazil, then the center of Zika cases—if they won a free ticket. Pregnant women were less willing (36%) than nonpregnant women (78%) to take this trip (Obenauer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…12 This is perhaps due to the study taking place approximately 3 years after the 2016 outbreak of Zika and relatively few Zika cases have been reported in Malaysia since 2016. Likewise, other studies among the public in the United States, 22 Germany, 23 and Western Europe 24 also similarly reported a low risk perception of contracting Zika among the public. Having a higher risk perception is associated with higher preventive-seeking behaviors.…”
Section: Disaster Medicine and Public Health Preparednessmentioning
confidence: 77%
“…Previously developed surveys have tended to be related to a specific mosquito species or MBV, rather than a broader scope of understanding behaviour towards mosquitoes and MBVs. Additionally, most surveys used in European studies are not validated, are Knowledge, Attitudes and Practices (KAP) surveys or are tailored to a certain population, rather than the general public 17 , 18 , 21 , 49 , 50 . We identified one Italian validated survey, created specifically to measure knowledge, attitude and behaviours towards Zika in the general population.…”
Section: Discussionmentioning
confidence: 99%